PRE-SWELLING PROCESS OF THE SURFACE MODIFIED MONTMORILLONITE (O-MMT) AS A STRATEGY TO ENHANCE EXFOLIATION AND DISPERSION - Abdul Hamid, A.R.; Osman, A.F.; Mustafa, Z.; Ananthakrishnan, R. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
The production of exfoliated polymer/clay based nanocomposites is crucial to obtain an actual benefit of nanoscale reinforcement in the polymer matrix. The objective of this study was to employ the pre-swelling process through the combination of magnetic stirring and ultra-sonication technique to produce more readily exfoliated O-MMT for the production of polymer nanocomposite. The effects of dispersant concentration on the thermal stability, structure and morphology of the pre-swelled O-MMT were studied. Results indicated that the pre-swelling process did not reduce the thermal stability of the O-MMT, showing that this method did not leach out or degrade the surface modifier of the O-MMT. Among all the pre-swelled O-MMTs, the one prepared using H2O/O-MMT ratio of 1:1 had the best thermal stability. As proved through the XRD analysis, this sample possesses larger basal spacing as compared to the origin O-MMT. FESEM analyses suggested that disorientation and misalignment of platelets occurred, forming ‘house of card’ structure. More porous and loosely packed platelets were obtained, which is predicted can allow better O-MMT dispersion and polymer chains intercalation during the formation of exfoliated polymer nanocomposite. Furthermore, the H2O/O-MMT ratio of 1:1 was selected as the best dispersant concentration to form the pre-swelled O-MMT.